Análise sociotécnica como instrumento de reflexão sobre transições energéticas: desafios e oportunidades da expansão fotovoltaica na China (1999-2020) - Bernardo Santos Lobato (2021)
This research aims to evaluate and analyze the forms considered to be the challenges and opportunities of the Energy Transition in China, more specifically, the implementation of photovoltaic systems in the electricity generation in a larger scale. In order to develop a sustainable sector, intermitente sources has been a central issue in this phenomenon, both at the national and international level, across policy, industrial and research’s actors. To the purpose of a in depht’s assessment on the issues involved, this work applied a framework in Sociotechnical Analysis: The Multilevel Perspective - MLP. The appropriation was made based on a Systematic Literature Review on the CAPES’s bases of journals, which links the subject ‘Energy Transition’ to the forms of 'sociotechnical'. The results point to the existence of different arrangements in the sector, based on different forms of discourses and agency. There are groups competing with each other for the national ‘framing’ on sustainability and are a consequence of both the international ‘pluralization’ of sustainable practices and the nationally fragmented internal condition. It is concluded that the Energy Transition’s national framing is due to a different forms of practices - not yet universalized - in the sector and, for that reason, the eletricity sector’s planning and the infrastructures involved become contradictory at this stage. These forms of conflict is given to different frames on the transition’s temporality and spatiality.